2008
DOI: 10.1248/cpb.56.1691
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Novel Phenolic Diterpenes from Podocarpus macrophyllus D. DON

Abstract: and from the leaves of Podocarpus macrophyllus var. maki (Japanese name: Rakanmaki), norditerpenes and totarols having cytotoxic activities against P388 murine leukemia cells have been reported by us. [5][6][7] In the present study, from the bark of Podocarpus macrophyllus D. DON, we isolated 8 new diterpenes along with known ones. This paper describes the isolation and structural elucidation of these new diterpenes and their antibacterial activities against oral pathogenic microorganisms. Results and Discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…[1] For instance, taxol, harringtonin, and camptothecin were identified from the Taxus, [2] Cephalotaxus, [3] and Camptotheca [4] species, respectively. Previously, a variety of flavonoids, [7] biflavonoids, diterpenoids (including norditerpenoid dilactones), [8] [9] and triterpenoids [10] have been reported from Podocarpus species. [5] There are thirteen species and three variants of Podocarpus in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] For instance, taxol, harringtonin, and camptothecin were identified from the Taxus, [2] Cephalotaxus, [3] and Camptotheca [4] species, respectively. Previously, a variety of flavonoids, [7] biflavonoids, diterpenoids (including norditerpenoid dilactones), [8] [9] and triterpenoids [10] have been reported from Podocarpus species. [5] There are thirteen species and three variants of Podocarpus in China.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Some of them are widely used in traditional medicine for treatment of pain, fever, and rheumatism. Previously, a variety of flavonoids, [7] biflavonoids, diterpenoids (including norditerpenoid dilactones), [8] [9] and triterpenoids [10] have been reported from Podocarpus species. Among them, most diterpenoids exhibited various biological activities, such as antitumor, [11] antilipemic, [12] and anti-oxidation activities.…”
Section: Introductionmentioning
confidence: 99%
“…Podocarpaceae1 is one of the most abundant evergreen trees distributed from Australia to the tropical and subtropical areas of Asia. Previous biological studies of the extracts from the leaves of this plant revealed high antibiotic as well as anticancer activities resulting from inumakiols,1a totarols,1b and other norditerpenes (Figure 1). 1c,d Recently, guided by a bioassay based on activator protein‐1 (AP‐1), the investigation on extracts of podocarpus latifolius at the National Cancer Institute (NCI) led to the isolation of three new inumakiol‐family diterpenes, namely cycloinumakiol ( 1 ), inumakal ( 2 ), and inumakoic acid ( 3 ) 2.…”
Section: Methodsmentioning
confidence: 99%
“…While the wood of this plant is used as timber for furniture and in paper-making, its edible fruits are consumed raw or cooked, and decoctions from its leaves are used in folk medicine to relieve rheumatism and painful joints [2]. Plants of the genus Podocarpus have been reported to exhibit a variety of biological activities ranging from plant-growth regulation [3, 4] to antibacterial [5] and antiproliferative [6–9] effects. These activities have been attributed mainly to their chemotaxonomic markers, the nor- and bisnorditerpene dilactones, referred to as the podolactones or nagilactones [10, 11].…”
Section: Introductionmentioning
confidence: 99%